Evaluation of the Effects of Lipoxin A4 and Resolvin D1 on the Severity of Transient Tachypnea of the Newborn: A Prospective Study - Çığrı, Emrah; Çatan İnan, Funda; Gülten, Sedat; Bildirici, Mehmet Akif; Gökkaya, Ayşe Ece; Asıleren, Metin; Yıldız, Fethiye; Kabukcu, Hilmi Onur (MDPI AG, 2025)
Objective: Transient tachypnea of the newborn (TTN) is a common condition observed in neonates. Since its management often requires intensive care and leads to maternal–infant separation, it is a major source of parental concern. The present study aimed to evaluate the effects of lipoxin A4 and resolvin D1 on the clinical course of TTN and to determine whether complete blood count parameters could serve as predictors of disease severity. Materials and Methods: A total of 62 neonates admitted to the neonatal intensive care unit with a diagnosis of TTN were included. According to Silverman scoring, infants were divided into a mild group (n = 31) and a severe group (n = 31). Lipoxin A4 and resolvin D1 levels, together with complete blood count parameters, were compared between the two groups. Logistic regression and receiver operating characteristic (ROC) curve analyses were performed to assess the predictive value of these parameters for the clinical course. Results: Serum lipoxin A4 (p = 0.005) and resolvin D1 (p = 0.002) levels were significantly higher in the mild group compared with the severe group, whereas the neutrophil-to-lymphocyte ratio (p = 0.044) and platelet-to-lymphocyte ratio (p = 0.027) were significantly lower. Resolvin D1 and the platelet-to-lymphocyte ratio were identified as significant predictors of severe disease. In predicting a mild course, lipoxin A4 demonstrated the highest sensitivity (80.6%), while resolvin D1 exhibited the highest specificity (87.1%). Conclusions: Lipoxin A4 and resolvin D1 appear to play a protective role in preventing severe clinical progression of transient tachypnea of the newborn.
Keywords: Article